Human-Rhesus macaque conflict at Pumdivumdi/ Tallokodi, Pokhara, West Nepal - Sharma, S.; Acharya, S. (Banko Janakari, 2018)
The study on conflict between human and Rhesus macaque was carried out at Pumdivumdi/Tallokodi in Pokhara valley in March, 2016. Questionnaire survey was carried out in 60 households to assess conflict, economic impact on livelihood of people and identify local deterrent method practiced. Purposive sampling method was used to select respondent for questionnaire survey. Majority of the respondents (58.3%) agreed that the damage of crops caused by monkeys was severe. According to 21.7% respondents, physical hurt and harassment were done by monkeys in the study area. There was a loss of more than NRs. 20,000 in 2015 in 32% of the total households surveyed. Maize was the most raided crop (31%) followed by potato (30%). Keeping dog in house (40%) was the most preferred local deterrent method followed by throwing stone and using catapult (21.7%). Banko Janakari A Journal of Forestry Information for Nepal Vol. 27, No. 2, 2017, Page: 46-50